Diversity and Local Contexts : Urban Space, Borders, and Migration - Krase, Jerome; Uherek, Zdeněk (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
In this book, an international team of urban anthropologists, sociologists, and ethnographers argue that politics, intergroup relations, and development in cities cannot be understood without reference to the local contexts that endow each city with specific characteristics. They also show how local urban economic, social, and cultural lives are influenced by powerful external forces. In these 'glocal' regards, the authors demonstrate how city images, borders, and social processes such as migration, tourism, and local development must be seen in broader contexts. The contributors examine them through the lenses of foreign investment, migration, and history. The volume takes an interdisciplinary approach and employs a range of theoretical perspectives and methodological approaches. Contributors' multidisciplinary expertise and insights about spaces and places are applied to nine unique cities across three continents.
Keywords: Social sciences.; Ethnography.; Sociology, Urban.; Emigration and immigration.; elektronické knihy; electronic books